Body image - Lankford, Ronald D., frey50 (Detroit : Lucent Books, 2010)
Examines where ideas about body image originate and the ways body image affects health and lifestyle.
Introduction: Appearance obsession -- What is body image? -- How does society and culture affect body image? -- Does mass media distort ideas of body image? -- Does advertising distort body image? -- Has body image become an obsession? -- Altering body image.
Keywords: Body image